Proteomic and phosphoproteomic profilings reveal distinct cellular responses during Tilapinevirus tilapiae entry and replication - Tuchakorn Lertwanakarn; Matepiya Khemthong; Piyathip Setthawong; Narumon Phaonakrop; Sittiruk Roytrakul; Sekkarin Ploypetch; Win Surachetpong (PeerJ)
Background Tilapia Lake virus (TiLV) poses a significant threat to global tilapia aquaculture, causing high mortality rates and severe economic losses. However, the molecular mechanisms underlying TiLV-host interactions remain largely unexplored. Methodology We investigated the proteomic and phosphoproteomic changes in two piscine cell lines, E-11 and RHTiB cells, following TiLV inoculation at different time points. Differential protein expressions at 10-min and 24-h post infection were selected for constructing protein-protein interactions and analyzing enriched pathways related to the viral entry and replication. Results Our findings revealed significant alterations in protein expression and phosphorylation states, highlighting distinct responses between the cell lines. In E-11 cells, TiLV infection suppressed proteins involved in the Janus kinase-signal transducer and activator of transcription and Fas-associated death domain protein-tumor necrosis factor receptor-associated factor pathways, leading to activation of nucleotide oligomerization domain signaling and apoptosis. In RHTiB cells, TiLV suppressed host cellular metabolism by reducing protein phosphatase activity to facilitate early viral entry, while later stages of infection showed increased activity of myosin heavy chain 9 and enhanced host immune responses via phosphorylation of ribosomal protein L17 and GTPase immunity-associated protein 7 (GIMAP7). Conclusion Our study suggested that TiLV employs different strategies to manipulate host cellular pathways depending on the cell type. Further studies are essential to validate these findings and ultimately facilitate the development of effective antiviral strategies.